EFFECTS OF VARIATIONS IN DIETARY ENERGY LEVELS ON THE GROWTH AND CARCASS QUALITY OF THE NIGERIAN DWARF SHEEP (1976)
A total of 76 animal experiments, involving young Nigerian Dwarf Sheep, were conducted to investigate the growth response to effects of varying levels of dietary energy. The studies also embraced digestibility trials and carcass evaluation. Results obtained appear to indicate that between the ages of 3 - 6 months, a daily intake of 107.1 kcal metabolizable energy was required for maintenance while from 6 - 9 months of age the requirement increased to 129.2 kcal per day. A growth requirement of 215 kca1 ME/day/W0.73kg and 1387 kcal ME/dayW0.73kg was obtained for animals between 3 - 6 months and 6 - 9 months respectively. An analysis of the pooled results seems to indicate that 134.04 kca1 ME per day and 647kca1/ME/day/W0.73kg was the requirement for maintenance and increase of 1 kg. live-weight respectively. Studies on digestibility of feeds revealed that the effects of variations in the type of ration on digestibility was less marked than the effects due to age of the animals. Crude fibre digestibility coefficient for the basal diet was about 68.04% for the older animals while the corresponding values for the younger animals ranged between 54.4% and 56.0%. values for the mixed diet and concentrate ration ranged from 68.3% to 77.45% and 71.3% to 79.5% respectively with the older animals while the corresponding values for the younger animals were in the range of 58:01% to 60.59% and 63:8% to 65.02%. Results of animal performance indicated that younger animals are capable of faster growth than older ones but the effect of low plane of nutrition as indicated by growth rates is more adversely felt by the younger animals. Thus the mean daily weight gains of the older animals were 79.6g, 83.8g, 82.2g, 55.7g for treatments A, B, C and D respectively while the corresponding values for the younger animals were 97.7g, 71.8g, 45.7g and 21.7g respectively. The carcass evaluation showed that dressing percentages and percentage flesh increase with age. At six months and in all treatments, the range was between 34.3% to 43.8% while at 9 months it rose to 49.7% to 60.8%. Percentage of flesh in the carcass has been shown to range from 62.6% to 66.2% at birth with a possible increase of about 0.7% to 0.9% per kg live-weight gain. The results of this study have shown that the younger animals are capable of faster growth and respond faster to high plane of nutrition but the effect of low plane of nutrition as indicated by growth rates of all animals on the lower energy level diets, is more adversely felt by the younger animals. It is to be noted that the early weaned lambs cannot survive on pasture alone. The results also were discussed in terms of the economics of production.